Primacy of surgery for colorectal cancer. (2nd April 2015) - Liang, J; Fazio, V; Lavery, I; Remzi, F; Hull, T; Strong, S; Church, J
Abstract: Background: The optimal technique for curative resection of colonic cancer includes high ligation of the mesenteric vessels, wide excision of the colonic mesentery and prevention of tumour cell spillage. This article reports results from the authors' institution for patients in whom complete mesocolic excision was performed long before the term was coined. Methods: Patients operated on for cure for primary adenocarcinoma of the colon between January 1994 and December 2004 were identified from a prospectively maintained, institutional review board-approved, colorectal cancer registry. Medical records and operation notes were reviewed. The primary outcomes were recurrence (local and distal) and age-adjusted 5-year survival. Results: Some 1013 patients (560 men and 453 women) were identified, with a median age of 69 (range 21–96) years. The most common location of the cancer was the sigmoid colon (32·9 per cent), followed by the caecum (26·7 per cent) and ascending colon (17·0 per cent). Operations were performed laparoscopically in 134 patients (13·2 per cent). Median duration of hospital stay was 7 (range 1–64, mean 8·2) days. Overall morbidity and mortality rates were 13·5 and 2·2 per cent respectively; there were 20 anastomotic leaks (2·0 per cent). Some 282 patients (27·8 per cent) had stage I, 386 (38·1 per cent) stage II and 345 (34·1 per cent) stage III disease. Median lymph node yield was 28·3 (range 0–241, mean 28·3), and 12 or more nodes were examined in 88·1 per cent of patients. Adjuvant chemotherapy was administered to 277 patients (80·3 per cent) with stage III disease. Overall local and distant recurrence rates at 5 years were 5·1 and 17·1 per cent respectively. The 5-year local recurrence rate was 2·2, 5·3 and 7·7 per cent for American Joint Committee on Cancer stages I, II and III respectively. Corresponding distant recurrence rates were 4·0, 14·7 and 30·5 per cent. The 5-year overall cancer-free age-standardized survival rate was 85·3 per cent. Five-year age standardized survival rates for patients with disease stages I, II and III were 97·7, 90·8 and 69·8 per cent respectively. Conclusion: These data define modern results of surgery for colonic cancer with conservative use of chemotherapy. Abstract : Excellent results before complete mesocolic excision was coined